Institutional isomorphism and community politicisation: A theoretical and empirical comparison between Indonesia and Japan - Seala Syah Alam; Sudarsono Hardjosoekarto; Arthur Josias Simon Runturambi; Chairul Muriman Setyabudi (Universitas Negeri Yogyakarta, 2026)
This research aims to explore how global pressures, international standards, and institutional structures affect the development and effectiveness of community politicisation, focusing on the similarities and differences between the two countries. This research uses a qualitative method, analysing secondary data from interviews, digital platforms, and public sources, complemented by textual analysis and social network analysis. These findings highlight the key role of isomorphism in standardising politicisation practices, with Indonesia and Japan both adopting community politicisation models to increase public trust and cooperation. However, significant differences were observed in the execution of these models, especially in the level of community involvement and the historical context of their implementation. While Japan's political system has matured through policies and structures such as